2001
DOI: 10.1144/pygs.53.3.177
|View full text |Cite
|
Sign up to set email alerts
|

Emplacement of the Great Whin Dolerite Complex and the Little Whin Sill in relation to the structure of northern England

Abstract: SUMMARY By definition, sills are concordant, tabular sheet-like bodies of igneous rock with the Great Whin Sill of northern England often quoted as a primary example. Analysis of surface and subsurface records of the Great Whin shows that it is seldom concordant over wide areas and usually rises and falls in the stratigraphical succession in gentle transgressions and abrupt jumps to new levels. The term ‘sill’ is not used here for the Great Whin complex, but is used for the related Little Whin Sill o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…3 and 4). Such geometries previously have been documented using 3D seismic data from the Faeroe-Shetland Basin (Davies et al 2002;Smallwood and Maresh 2002) and in classic onshore localities such as the Karoo of South Africa (Du Toit 1920;Chevalier and Woodford 1999), the Whin Sill (Francis 1982;Johnson and Dunham 2001), the Midland Valley Sill (Francis 1982) and in Tasmania (Leaman 1975). The largest sills in the North Rockall Trough displaying this geometry are roughly radially symmetrical and approximately 5 km wide (cf.…”
Section: Sill Complex Geometriesmentioning
confidence: 63%
See 2 more Smart Citations
“…3 and 4). Such geometries previously have been documented using 3D seismic data from the Faeroe-Shetland Basin (Davies et al 2002;Smallwood and Maresh 2002) and in classic onshore localities such as the Karoo of South Africa (Du Toit 1920;Chevalier and Woodford 1999), the Whin Sill (Francis 1982;Johnson and Dunham 2001), the Midland Valley Sill (Francis 1982) and in Tasmania (Leaman 1975). The largest sills in the North Rockall Trough displaying this geometry are roughly radially symmetrical and approximately 5 km wide (cf.…”
Section: Sill Complex Geometriesmentioning
confidence: 63%
“…Apart from Leaman (1975), the majority of outcrop-based studies on sill intrusion have suggested that sills are dyke sourced. Consequently, one would expect an alignment of sill complexes corresponding to the preferred dyke orientation across the region (Francis 1982;Chevalier and Woodford 1999;Johnson and Dunham 2001). However, evidence for dykes feeding sills is often lacking (e.g.…”
Section: Models For Sill Emplacementmentioning
confidence: 99%
See 1 more Smart Citation
“…In some cases dykes are seen to change into sills, but the feeders for sills are often poorly exposed in the field so that a clear connection between the feeder and the sill is commonly lacking (Johnson and Dunham, 2001). In this respect, the Njardvik Sill offers an exceptionally clear example for the feeding relationships between inclined sheets and the sills they acted as feeders for.…”
Section: Dykes As Feeders For Sillsmentioning
confidence: 99%
“…1) along the southern margin of the coalfield occurred at 292F20 Ma from hot (CAI of 3 suggests 110 8C, Armstrong and Purnell, 1993) sulphate-rich NaCl brines (Sawkins, 1966;Smith and Phillips, 1974;Smith, 1980). Thus, the introduction of sulphur-rich fluids was associated with late Westphalian-early Permian Variscan transpressional tectonics from the south, which led to uplift, faulting and folding, and the imposition of a regional dip of up to 58 to the east and northeast in Northumberland (Mills and Holliday, 1998;Johnson and Dunham, 2001). As a result, late stage Variscan compressional tectonics, at about 280 Ma, may have induced the expulsion of hot sulphur-rich fluids from depth and large-scale fluid movement northwards and upwards through the Coal Measures towards the basin margin, possibly along basin margin faults (Mills and Holliday, 1998).…”
Section: Sulphur Isotopic Composition and The Source Of Sulphurmentioning
confidence: 99%